Albania : First Post-Program Monitoring-Press Release; Staff Report; and Statement by the Executive Director for Albania. (IMF Staff Country Reports; Country Report ;, 2020)
Albania continues to be severely affected by the aftermath of the November 2019 earthquake and the COVID-19 pandemic. The authorities responded promptly to the shocks, and macroeconomic and financial stability have so far been maintained. The economy is expected to contract sharply in 2020, followed by a gradual recovery in 2021-22. The outlook is subject to major uncertainty and rising downside risks as a second wave is gripping many countries in Europe. Albania's capacity to repay the Fund is adequate, but risks have risen in light of the shocks. Aside from a more severe pandemic, key risks stem from elevated public deficits and debt, weaknesses in public finances, and a relatively high level of non-performing loans (NPLs) and euroization.